2015
DOI: 10.7863/ultra.15.14.11014
|View full text |Cite
|
Sign up to set email alerts
|

Using Ultrasound to Enhance Medical Students' Femoral Vascular Physical Examination Skills

Abstract: The addition of ultrasound teaching to traditional physical examination instruction enhanced medical student competency and confidence with the femoral vascular examination. However, understanding of anatomy may require emphasis on precourse didactic material, but further study is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 22 publications
0
35
0
1
Order By: Relevance
“…Neither approach looks at an entire course in a holistic fashion. Study methods used were survey and questionnaire responses, pretests and posttests designed explicitly for a POCUS cohort, and US‐specific OSCEs, which were separate from a traditional curriculum . Two recent studies suggest benefits of pairing US curricula with physical examination courses, but overall the current literature offers a piecemeal approach to understanding the effects of POCUS in UME, and a more general approach is needed to define particular ways and specific areas in which POCUS aids a full curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither approach looks at an entire course in a holistic fashion. Study methods used were survey and questionnaire responses, pretests and posttests designed explicitly for a POCUS cohort, and US‐specific OSCEs, which were separate from a traditional curriculum . Two recent studies suggest benefits of pairing US curricula with physical examination courses, but overall the current literature offers a piecemeal approach to understanding the effects of POCUS in UME, and a more general approach is needed to define particular ways and specific areas in which POCUS aids a full curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Point‐of‐care ultrasound (POCUS) is a potentially powerful adjunct to undergraduate medical education (UME), with the capacity to enhance and reinforce students' understanding of basic sciences, physical examination maneuvers, procedural confidence, and diagnostic accuracy . Advocates of these benefits suggest that POCUS teaching to beginner trainees may ultimately affect patient care .…”
mentioning
confidence: 99%
“…Dinh et al [46] found that students that had ultrasound incorporated into their physical examination curriculum obtained greater OSCE scores than a cohort of students that took the exams prior to the introduction of ultrasound, in the same medical school. The educational interventions found here range from those that teach students to scan a wide range of anatomy [47,48] or regional anatomy [49] to more focused exams of the vascular [50][51][52], abdominal [53][54][55], head and neck [56], cardiac [57,58] and respiratory [59] systems. Some institutions taught students ultrasound-specific protocols such as FAST [60][61][62] or USEFUL [63] scans.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…US has been used in various studies to improve medical students' clinical examination skills [13][14][15][16]. The majority of the studies focused on students' skills to detect liver margins [13,14], inferior limit of the lung or thyroid size [15], or to localize femoral artery and vein [16].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies focused on students' skills to detect liver margins [13,14], inferior limit of the lung or thyroid size [15], or to localize femoral artery and vein [16].…”
Section: Discussionmentioning
confidence: 99%